Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content: 1. Factors affecting the shadow economy and their impact on economic growth in the Kingdom of Saudi Arabia during the period (2007-2021) Dr. Vivian Mohammed saleh Nasrulddin, Mrs. Hessa saad Alshahrani 2. The Impact of the Government Role in the Development of Small and Medium Enterprises in the Arab Republic of Egypt (Applying to Damietta Governorate) Dr. Ehab Mohamed Afifi, Prof. Mohamed Najib Abdel-Fattah , Dr. Iman Mustafa Muslim 3. The effect of job satisfaction on the level of productivity among government health sector nurses in Riyadh A study of its application to Al-Iman General Hospital in Riyadh Mr. Saleh Mohammed Al-Zoghaibi 4. The Right of The Individual to The Safety of His physical and Psychological Being During the Investigation in Accordance with International Conventions and Islamic Law (Comparative Study) Dr. Abdelgadir Abdelrhman-Abdelgadir 5. Judicial jurisprudence issued by Sharia courts in family reform Dr. Waleed Khaled Baklizi 6. Impact of Accounting Conservatism on Improving and Evaluating The efficiency of the financial performance of Islamic banks (An analytical study on Faisal Islamic Bank during 2011 - 2015) Prof. Huda Diayb Ahmed, Dr. Randa Abdelhamied Mohammed, Dr. Badralden Mohammed Yhaya 7. Critical Success Factors of Business Intelligence System in Organizations Eng. Talha Abed-Al-Fattah Mashayekh , Dr. Hashem Mohammed Al-Aidaros , Dr. Haitham Zaker Khoj 8. Protecting Child Refugees from Violence: Between Legal Texts and Practical Experiences Co-Prof. Maya Hasan Khater 9. The application of the quick response manufacturing system (QRM) in Sudanese industrial companies and its impact on reducing costs and achieving competitive advantage (For the period 2017-2022) (Analytical study) Dr. Amira Abdalrhman Almekki